2019
DOI: 10.1186/s12910-019-0425-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethical considerations in prehospital ambulance based research: qualitative interview study of expert informants

Abstract: BackgroundPrehospital ambulance based research has unique ethical considerations due to urgency, time limitations and the locations involved. We sought to explore these issues through interviews with experts in this research field.MethodsWe undertook semi-structured interviews with expert informants, primarily based in the UK, seeking their views and experiences of ethics in ambulance based clinical research. Participants were questioned regarding their experiences of ambulance based research, their opinions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…It has been suggested that the prehospital setting will be the next great clinical 'laboratory' for advancing emergency treatments (7). Through this study we hoped to gain further insight into the role of paramedics in facilitating research and in particular any ethical considerations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been suggested that the prehospital setting will be the next great clinical 'laboratory' for advancing emergency treatments (7). Through this study we hoped to gain further insight into the role of paramedics in facilitating research and in particular any ethical considerations.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has suggested that length of service and education has an impact on paramedics' willingness to participate in research, with so-called 'old school' paramedics being less willing to be involved in recruiting patients onto research or taking part in research themselves as participants (7,16). This did not appear to be the case in this study where there was an equal ratio of short to long serving paramedics (> 10 years, n = 7; <10 years, n = 8) (see Table 1).…”
Section: Demographic Datamentioning
confidence: 99%
“…We chose this model because previous research has demonstrated the difficulties involved in seeking informed consent in emergency medical research. [17][18][19][20][21][22][23][24][25][26] Largent et al provide an alternative to unsatisfactory consent processes used in this context. Furthermore, their model continues to be cited regularly in the emergency research literature.…”
Section: Comparison Of Ethical Framework With the Consent Substitute Modelmentioning
confidence: 99%
“…We compared the five conditions of the consent substitute model with the emergency research provisions within international and national ethical frameworks, to determine whether it could be employed by researchers adhering to these frameworks. We chose this model because previous research has demonstrated the difficulties involved in seeking informed consent in emergency medical research 17–26 . Largent et al provide an alternative to unsatisfactory consent processes used in this context.…”
Section: Comparison Of Ethical Framework With the Consent Substitute Modelmentioning
confidence: 99%
“…From a conduct perspective, the importance of timeliness with regard to accessing the patient, randomisation (often remotely) and delivery of the intervention is also key. The broader ethical considerations relating to recruitment, capacity and consent under the challenging circumstances surrounding major trauma also need to be considered [ 12 ]. Futhermore, the complex nature of traumatic injuries can result in patients receiving multiple interventions (that may not be standardised in or between trauma centres) both pre and within hospital, making it very difficult to disentangle intervention effect on outcomes such as mortality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%